2008
DOI: 10.1080/07315724.2008.10719725
|View full text |Cite
|
Sign up to set email alerts
|

A Mediterranean Dietary Style Improves Calcium Utilization in Healthy Male Adolescents

Abstract: A varied diet based on Mediterranean diet patterns during adolescence greatly improves dietary calcium utilization, which may help to maximize the peak bone mass and prevent related diseases, such as osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 41 publications
0
43
0
1
Order By: Relevance
“…It has been shown that dietary calcium utilization during adolescence may be greatly improved by a diet based on the Mediterranean patterns (Seiquer et al, 2008). Compared with the consumption of their habitual diets, adolescents significantly increased the absorption and retention of the dietary calcium, and, as a consequence, calcium utilization efficiency was significantly improved when subjects consumed the Mediterranean diet.…”
Section: The Mediterranean Dietmentioning
confidence: 94%
See 4 more Smart Citations
“…It has been shown that dietary calcium utilization during adolescence may be greatly improved by a diet based on the Mediterranean patterns (Seiquer et al, 2008). Compared with the consumption of their habitual diets, adolescents significantly increased the absorption and retention of the dietary calcium, and, as a consequence, calcium utilization efficiency was significantly improved when subjects consumed the Mediterranean diet.…”
Section: The Mediterranean Dietmentioning
confidence: 94%
“…On the contrary, low phosphorus and high sodium and caffeine intake are associated with increased urinary calcium (Kiel et al, 1990;Brunette et al, 1992;Weisinger & Bellorin-Font, 1998). With an adequate diet, calcium bioavailability is favored, reaching values around 36.5% for boys and 29.6% for girls, or even higher when diets provide suitable amounts of the mineral Seiquer et al, 2008). Thus, as mentioned above, the dietary habits of adolescents are an important factor to meet calcium requirements and, consequently, needs for pubertal growth.…”
Section: Calciummentioning
confidence: 99%
See 3 more Smart Citations